Answer: C
Step-by-step explanation:
Slope-Intercept form of an equation is y = mx + b
- m is slope (rise over run)
- b is y-intercept (where it crosses the y-axis)
Red line:
It crosses the y-axis at -3 so b = -3
Now count the rise over run from the b (0, -3) to another point (I chose (1, -1) because it was the next point on a lattice line). The rise is 2 and the run is 1. So. rise over run is 2/1 ⇒ m = 2
Equation: y = 2x - 3
Yellow line:
Follow the same steps as the Red line to get b = 1 and m = -2
Equation: y = -2x + 1